Spectrometers with Polarizing Attachment and Camera Attachment - Wm. Gaertner & Company (Instruments of Precision Laboratory Apparatus, M-L Catalog, 1911)
Top figure is a laboratory spectrometer with a polarizing attachment. Lower figure is a spectrometer with a third arm and camera attachment.
Keywords: Spectrometer; Scientific apparatus and instruments; Laboratories--Equipment and supplies; Measuring instruments